2023
DOI: 10.5056/jnm23066
|View full text |Cite
|
Sign up to set email alerts
|

2022 Seoul Consensus on Clinical Practice Guidelines for Functional Constipation

Abstract: Chronic constipation is one of the most common digestive diseases encountered in clinical practice. Constipation manifests as a variety of symptoms, such as infrequent bowel movements, hard stools, feeling of incomplete evacuation, straining at defecation, a sense of anorectal blockage during defecation, and use of digital maneuvers to assist defecation. During the diagnosis of chronic constipation, the Bristol Stool Form Scale, colonoscopy, and a digital rectal examination are useful for objective symptom eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 297 publications
0
6
0
Order By: Relevance
“…It is a complex neuroendocrine network, including the central nervous system, intestinal nervous system and autonomic nervous system, which can maintain brain-intestinal interaction and information exchange among various systems (Daniali et al, 2020;Muller-Lissner et al, 2017). Studies (Brenner et al, 2023;Cho et al, 2023) have shown that risk factors for functional constipation include advanced age, low-fiber diet, low socioeconomic status, immobility, abdominal or pelvic surgery, and multidrug therapy. It has been reported (Dzierzanowski & Cialkowska-Rysz, 2015) that the behavioral causes of patients with constipation Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…It is a complex neuroendocrine network, including the central nervous system, intestinal nervous system and autonomic nervous system, which can maintain brain-intestinal interaction and information exchange among various systems (Daniali et al, 2020;Muller-Lissner et al, 2017). Studies (Brenner et al, 2023;Cho et al, 2023) have shown that risk factors for functional constipation include advanced age, low-fiber diet, low socioeconomic status, immobility, abdominal or pelvic surgery, and multidrug therapy. It has been reported (Dzierzanowski & Cialkowska-Rysz, 2015) that the behavioral causes of patients with constipation Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…The use of magnesium salts and polycarbophil were greatly reduced in patients with advanced CKD. Magnesium salts act as osmotic agents but are avoided due to the risk of hypermagnesemia in patients with CKD 44 . Half of the patients on PD taking a polycarbophil as first-line therapy switched to the osmotic agent lactulose.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the treatments of FC include lifestyle modification, transanal irrigation, pharmacological interventions, biofeedback therapy, and probiotics (17)(18)(19)(20)(21). Among these treatments, nonpharmacological management is the first step in the treatment of FC.…”
Section: Introductionmentioning
confidence: 99%